Malnutrition status and other common comorbidities among inmates of childcare homes in puducherry, India - An Analytical Cross-Sectional study - Madhu Karam; Swaroop Kumar Sahu; Sathish Rajaa (Elsevier, 2021)
Background: Inmates of child care institutions constitutes a vulnerable group. It is important to monitor their health status. This study aimed at estimating the prevalence of malnutrition and other common comorbidities among them. Methods: This is an Analytical Cross-Sectional study done in randomly selected twelve childcare institutions in Puducherry. All eligible 563 inmates, aged 5-18 years, from the selected institutions were included in the study. Pretested structured questionnaire was used to collect data. Nutrition status of participants were assessed using WHO BMI-for-age and Height-for-age growth charts. Inmates were clinically examined for nutrition status, vitamin deficiencies, skin conditions and goiter. Assessment of common comorbidities was done using modified Rashtriya Bal Swasthya Karyakram (RBSK) questionnaire. Inmates were also assessed for Presumptive Tuberculosis. Results: The prevalence of undernutrition was 39.4% (95% CI 35.48-43.53). Prevalence of thinness was 27% (95% CI 23.5-30.8) and prevalence of stunting was 20% (95% CI 16.9-23.5). Dental problems were found in 61% of the study population. Other nutritional deficiencies found on examination were palmar pallor (26.8%), Goiter (2%) and Bitot spots (0.7%). Around 4.6% of inmates reported that they had cough for 2 weeks or more and 3.7% had history of contact with a known case of Tuberculosis. Conclusion: The common comorbidities among the inmates were dental problems, undernourishment and anemia. There is need for regular health education and screening for these conditions for timely identification and initiation of appropriate interventions. There is also a need for symptomatic screening for early identification and reporting of presumptive Tuberculosis cases.